Intermittent hypoxia research in the former Soviet Union and the Commonwealth of Independent States: History and review of the concept and selected applications - Serebrovskaya, T. (High Altitude Medicine & Biology, 2002)
This review aims to summarize the basic research in the field of intermittent hypoxia in the Soviet Union and the Commonwealth of Independent States (CIS) that scientists in other Western countries may not be familiar with, since Soviet scientists were essentially cut off from the global scientific community for about 60 years. In the 1930s the concept of repeated hypoxic training was developed and the following induction methods were utilized: repeated stays at high-mountain camps for several weeks, regular high altitude flights by plane, training in altitude chambers, and training by inhalation of low-oxygengas mixtures. To the present day, intermittent hypoxic training (IHT) has been used extensively for altitude preacclimatization; for the treatment of a variety of clinical disorders, including chronic lung diseases, bronchial asthma, hypertension, diabetes mellitus, Parkinson`s disease, emotional disorders, and radiation toxicity, in prophylaxis of certain occupational diseases; and in sports. The basic mechanisms underlying the beneficial effects of IHT are mainly in three areas: regulation of respiration, free-radical production, and mitochondrial respiration. It was found that IHT induces increased ventilatory sensitivity to hypoxia, as well as other hypoxiarelated physiological changes, such as increased hematopoiesis, alveolar ventilation and lung diffusion capacity, and alterations in the autonomic nervous system. Due to IHT, antioxidant defense mechanisms are stimulated, cellular membranes become more stable, Ca21 elimination from the cytoplasm is increased, and O2 transport in tissues is improved. IHT induces changes within mitochondria, involving NAD-dependent metabolism, that increase the efficiency of oxygen utilization in ATP production. These effects are mediated partly by NO-dependent reactions. The marked individual variability both in animals and humans in the response to, and tolerance of, hypoxia is described. Studies from the Soviet Union and the CIS significantly contributed to the understanding of intermittent hypoxia and its possible beneficial effects and should stimulate further research in this direction in other countries.